Endoscopic papillectomy for ampullary lesions in patients with familial adenomatous polyposis compared with sporadic lesions: a propensity score-matched cohort - Vu Trung, Kien; Abou-Ali, Einas; Caillol, Fabrice; Paik, Woo H.; Napoleon, Bertrand; Masaryk, Viliam; van der Wiel, Sophia E.; Pérez-Cuadrado-Robles, Enrique; Musquer, Nicolas; Halimi, Asif; Soares, Kevin; Souche, Francois R.; Seyfried, Steffen; Petrone, Maria C.; Crippa, Stefano; Kleemann, Tobias; Albers, David; Weismüller, Tobias J.; Dugic, Ana; Meier, Benjamin; Wedi, Edris; Schiemer, Moritz; Regner, Sara; Gaujoux, Sebastien; Hollenbach, Marcus; ESAP Study Group; Auriemma, Francesco; Gulla, Aiste; Karam, Elias; Giovannini, Marc; Ratone, Jean-Philippe; Will, Uwe; Saadeh, Rita; Bruno, Marco J.; Deprez, Pierre; Arnelo, Urban; Haraldsson, Erik; Waldthaler, Alexander; Leung, Galen; Schattner, Mark A.; Jarnagin, William R.; Wang, Tiegong; Fabre, Jean M.; Kähler, Georg; Mariani, Alberto; Zaccari, Piera; Belfiori, Giulio; Falconi, Massimo; Partelli, Stefano; Repici, Alessandro; Anderloni, Andrea; Laukkarinen, Johanna; Hoffmeister, Albrecht; Rosendahl, Jonas; Schumacher, Brigitte; Barbier, Louise; Heling, Dominik; Muehldorfer, Steffen; Truant, Stéphanie; Caca, Karel; Tantau, Marcel; Salzmann, Katrin; David, Patrice; Schmidt, Arthur; Piardi, Tullio; Löhr, J. Matthias; Gagniére, Johan; Miutescu, Bogdan P.; Berger, Arthur; Schemmer, Peter; Heise, Christian; Sandru, Vasile; Ahola, Reea; Dinis-Ribeiro, Mario; Gonçalves, Tiago Cúrdia; Wichmann, Dörte (Endoscopy, 2023)
Background Familial adenomatous polyposis (FAP) is a rare inherited syndrome that predisposes the patient to cancer. Treatment of FAP-related ampullary lesions is challenging and the role of endoscopic papillectomy has not been elucidated. We retrospectively analyzed the outcomes of endoscopic papillectomy in matched cohorts of FAP-related and sporadic ampullary lesions (SALs).Methods This retrospective multicenter study included 1422 endoscopic papillectomy procedures. Propensity score matching including age, sex, comorbidity, histologic subtype, and size was performed. Main outcomes were complete resection (R0), technical success, complications, and recurrence.Results Propensity score matching identified 202 patients (101 FAP, 101 SAL) with comparable baseline characteristics. FAP patients were mainly asymptomatic (79.2 % [95 %CI 71.2–87.3] vs. 46.5 % [95 %CI 36.6–56.4]); P < 0.001). The initial R0 rate was significantly lower in FAP patients (63.4 % [95 %CI 53.8–72.9] vs. 83.2 % [95 %CI 75.8–90.6]; P = 0.001). After repeated interventions (mean 1.30 per patient), R0 was comparable (FAP 93.1 % [95 %CI 88.0–98.1] vs. SAL 97.0 % [95 %CI 93.7–100]; P = 0.19). Adverse events occurred in 28.7 %. Pancreatitis and bleeding were the most common adverse events in both groups. Severe adverse events were rare (3.5 %). Overall, 21 FAP patients (20.8 % [95 %CI 12.7–28.8]) and 16 SAL patients (15.8 % [95 %CI 8.6–23.1]; P = 0.36) had recurrence. Recurrences occurred later in FAP patients (25 [95 %CI 18.3–31.7] vs. 2 [95 %CI CI 0.06–3.9] months).Conclusions Endoscopic papillectomy was safe and effective in FAP-related ampullary lesions. Criteria for endoscopic resection of ampullary lesions can be extended to FAP patients. FAP patients have a lifetime risk of relapse even after complete resection, and require long-time surveillance.